VIDEO DATA IMAGE COMPRESSION USING LIFTING SCHEME WAVELET-BASED TRANSFORM - Kanger, Ebtesam; Abaas, Ban; Yahya, Inas; Abed Azeez, Nassr (Iraqi Journal of Science, 2024)
Video data image compression is now essential for application such as storage andtransmission in image sequence. This paper proposes a new lifting scheme waveletbasedtransform for compressed the data image more over is used to improve thequality of the resulted decompressed image. Also a new adaptive motion estimationtechnique was produce.